Tendencije razvoja telefonskog prometa između SR Hrvatske i Evrope - Acinger, Krešimir; Jaram, Slavko (Promet - Traffic&Transportation, 2012)
The authors review the tendencies of development of telephone communications of Croatia with European countries which is rather important for the planning of development and introduction of the information systems in the international traffic. The development of telephone communications systems and the introduction of new attractive telecommunications services will give an urge to the future and continued growth of telephone traffic, while an inadequately developed network of systems can have adverse repercussions upon the development of international trade, tourist trade and overall economy and industry.